2022
DOI: 10.1590/fst.49021
|View full text |Cite
|
Sign up to set email alerts
|

Performance of sesame straw cellulose, hemicellulose, and lignin biochars as adsorbents in removing benzo(a)pyrene from edible oil

Abstract: The safety problems related to the occurrence of benzo(a)pyrene in edible oil have been a major threat to human health, and now significant attention has been to remove benzo(a)pyrene. So in this work, cellulose, hemicellulose, and lignin biochars were prepared, and then were used to remove benzo(a)pyrene from contaminated oil. Based on the nitrogen adsorption/desorption isotherms and the scanning election micrographs, the modified biochars had a huge specific surface area of 983.50-1915.55 m 2 /g and a well-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Sesame straw carbon and modified carbon Three kinds of carbon were produced from sesame straw powder using methods described in the literature (Yang et al, 2022). Zinc chloride-activated carbon was prepared as follows, sesame straw powder was mixed with zinc chloride in a ratio of 1:2 (w/w).…”
Section: Preparation Of Decolorizersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sesame straw carbon and modified carbon Three kinds of carbon were produced from sesame straw powder using methods described in the literature (Yang et al, 2022). Zinc chloride-activated carbon was prepared as follows, sesame straw powder was mixed with zinc chloride in a ratio of 1:2 (w/w).…”
Section: Preparation Of Decolorizersmentioning
confidence: 99%
“…Sesame straw, a by‐product of sesame seed production, can be used as a type of carbon in the decolorization. It has been reported that modified sesame straw carbon has a promising means of removing the harmful substance benzo(a)pyrene from sesame oil (Yang et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%